2015
DOI: 10.1007/s11665-015-1689-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Texture, and Deep Drawability Under Two Different Cold-Rolling Processes in Ferritic Stainless Steel

Abstract: In the present study, the through-thickness texture evolution and grain colony distribution in ferritic stainless steel under two different cold-rolling processes have been investigated with the aim to enhance deep drawability. It was shown that in the case of conventional cold-rolling process, at the surface, midthickness between the surface and the center, and center layers, all the textures consisted of very sharp afiber and weak c-fiber with a peak at {111}AE110ae after cold rolling, and non-uniform c-fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Due to the segregation of γ‐fiber and α‐fiber textures, a high adjacent probability for γ‐fiber and α‐fiber texture orientations provides more opportunities for occurring large fraction of CSL boundaries. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…Due to the segregation of γ‐fiber and α‐fiber textures, a high adjacent probability for γ‐fiber and α‐fiber texture orientations provides more opportunities for occurring large fraction of CSL boundaries. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…2) favored the formation of the {111}〈112〉 components after annealing. According to Gao et al 19 , the weak texture after cold rolling is unfavorable for the intensification of the recrystallization texture. Thus, it could be concluded that the stronger texture after 80% of reduction improved the γ-fiber intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 11 shows the formability for Sn-bearing ferritic stainless steel with different HBA temperatures. The average plastic strain ratio (r) and earring coefficient (Δr) are important indexes in evaluating the formability of ferritic stainless steels [24,25], and these parameters are determined in our present study so as to assess the formability of our experimental steel. As shown in the figure, the average r value increases first and then decreases with the rising HBA temperature, and it reaches a maximum of 1.71 when HBA temperature is 950 °C.…”
Section: Formabilitymentioning
confidence: 99%
“…The Δr value also has a close relationship with crystallographic texture, and distinct orientations have distinct Δr values. In body-centered cubic (bcc) metals, {111} <110> and {111} <112> orientations have a small Δr value, while {001} <110> and{112} <110> orientations possess a larger Δr value [25]. Combining with the ODFs of the final sheets, the {111} <112> recrystallization texture slightly increases first and then significantly decreases with the rising HBA temperature, and the texture intensity reaches a maximum when it is at 950 °C.…”
Section: Formabilitymentioning
confidence: 99%